Relationship between nutrition knowledge, education and other determinants of food intake and lifestyle habits among adolescents from urban and rural secondary schools in Tyrol, Western Austria. Issue 17 (17th December 2020) - Egg, Sabrina; Wakolbinger, Maria; Reisser, Anna; Schätzer, Manuel; Wild, Birgit; Rust, Petra
Abstract: Objective: The aim of this study was to investigate the association of the number of hours of nutrition education and teachers' qualifications with nutrition knowledge and dietary behaviour in students. Design: In this representative cross-sectional study, socio-demographic data, anthropometric measurements, socio-economic status (SES), physical fitness, nutrition knowledge and eating habits were assessed. Differences between groups were tested by χ 2 and t tests. Multiple linear and logistic regression modelling was used to examine the relationship between demographic characteristics, lifestyle and dietary behaviours, nutrition knowledge, nutrition-trained teachers and number of nutrition lessons. Setting: Sixteen secondary schools in urban ( n 6) and rural regions ( n 10) of Tyrol, Western Austria. Participants: Students ( n 513) aged 14·2 (sd 0·7) years. Results: Higher nutrition knowledge was significantly associated with attending rural school ( P = 0·001), having no migration background ( P < 0·001), (very) good physical activity behaviour ( P = 0·040), non-trained teacher ( P = 0·006) but higher number of hours of nutrition education ( P = 0·013). Regression models showed that higher nutrition knowledge was independently associated with lower intake of meat and iced tea and higher intake of vegetables and plant-based oils. A higher amount of nutrition education (h/week) was significantly associated with higher intake of dark (wholegrain) bread, lower intake of meat and of energy drinks sweetened with sweeteners. Conclusions: Our results suggest that more hours in nutrition education result in higher nutrition knowledge and greater nutrition literacy, which may lead to health-promoting dietary habits. School-based nutrition education can be seen as preventive measure to increase nutritional competences in adolescents independent of their SES.